2022
DOI: 10.3390/cells11071112
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs Contained in Extracellular Vesicles Cargo Contribute to the Progression of Idiopathic Pulmonary Fibrosis: An In Vitro Aproach

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive lung disease. Lesions in the lung epithelium cause alterations in the microenvironment that promote fibroblast accumulation. Extracellular vesicles (EVs) transport proteins, lipids, and nucleic acids, such as microRNAs (miRNAs). The aim of this study was to characterize the differentially expressed miRNAs in the cargo of EVs obtained from the LL97 and LL29 fibroblast cell lines isolated from IPF lungs versus those derived from the CCD19 fibroblast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…They regulate cell–cell signaling [ 141 , 142 ]. EV-carried miRNA can contribute to fibrosis [ 143 , 144 , 145 ] as highlighted by Let-7 miRNA. Let-7 targets IGF1, which is overexpressed in alveolar macrophages and can stimulate collagen production in IPF [ 146 , 147 ].…”
Section: Macrophages In Fibrosismentioning
confidence: 99%
“…They regulate cell–cell signaling [ 141 , 142 ]. EV-carried miRNA can contribute to fibrosis [ 143 , 144 , 145 ] as highlighted by Let-7 miRNA. Let-7 targets IGF1, which is overexpressed in alveolar macrophages and can stimulate collagen production in IPF [ 146 , 147 ].…”
Section: Macrophages In Fibrosismentioning
confidence: 99%
“…Due to their accumulation in body fluids and their ability to participate in disease mechanisms, EVs are regarded as interesting targets to develop both novel therapies and also diagnosis/prognostic tools (Soekmadji et al, 2020). We and others demonstrated the crucial role of EVs during pulmonary fibrosis (Martin-Medina et al, 2018; Njock et al, 2019; Parimon et al, 2019; Santos-Alvarez et al, 2022). These vesicles accumulate within the lungs of patients with IPF and can be collected in several body fluids such as BALF, sputum or urine (Elliot et al, 2022; Martin-Medina et al, 2018; Njock et al, 2019).…”
Section: Discussionmentioning
confidence: 59%
“…Considerable efforts have been undertaken to investigate EV’s cargo and their corresponding biological function. In lung fibrosis several unbiased approaches identified specific cargo signatures of fibrotic vesicles mainly for microRNAs (Njock et al, 2019; Parimon et al, 2019; Santos-Alvarez et al, 2022). In particular, increasing levels of specific miRNAs transported by extracellular vesicles are linked to the activation of pathological signaling pathways and correlate with declined lung function in patients (Njock et al, 2019; Parimon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of miRNAs as therapeutic drugs is a possibility yet to be verified in clinical trials, at present, more investigations have focused on the therapeutic role of miRNAs derived from extracellular vesicles (EVs). More studies have investigated the use of miRNAs from mesenchymal stem cells (MSC-EVs) from chronic respiratory diseases; these studies have shown promising results [ 178 , 179 , 180 ]. It is also important to highlight that at present not only the miRNAs are under evaluation as potential therapeutic targets, but the non-coding RNAs as long non-coding RNAs (lncRNAs) are also being explored for their possible clinical application in respiratory diseases [ 29 , 30 ], which underline the actual relevance of this type of molecule.…”
Section: Discussionmentioning
confidence: 99%